แบบจำลองการคาดคะเนของผลการระเบิดในเหมืองหิน เพื่อให้ได้การแตกหักที่เหมาะสมที่สุด : รายงานฉบับสมบูรณ์ - สง่า ตั้งชวาล (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
Development works for large scale quarries are usually excavated by bench blasting method. The main reason is that this blasting method is giving high efficiency, economics and can control their blast impacts and damage within better limit than other methods. A packet program in which it was developed for this research work has been divided in 3 parts. The first part of this program shows the preliminary blast planning at the quarry face. The second part shows the calculated results of fragmentation when the rock mass was subjected to the pressure from blasting wave pulse. This part will calculate the size of fragments and their percentage. The third part of program shows the analysis results of quarry planning and explosive selection choices. These results are concurrent analyzed with the total costs of blasting works. Thus the blast efficiency is depend on the optimum fragmentation of blasted rock.